Clinical aspects of motor neurone disease. (September 2016) - Hobson, Esther V.; Harwood, Ceryl A.; McDermott, Christopher J.; Shaw, Pamela J.
Abstract: Motor neurone disease (MND) is a disabling and ultimately fatal disease of the motor system, with few effective treatments. Considerable heterogeneity is observed in the clinical motor features of MND, with extra-motor manifestations now also recognized as part of the condition. Diagnosis remains clinical, with appropriate investigations to exclude mimics. The multidisciplinary team approach is at the centre of holistic management of patients and families and can improve survival and quality of life. Although the disease remains incurable, survival benefit has been observed with the use of non-invasive ventilation and riluzole. Recent identification of genetic causes of MND, particularly the C9orf72 hexanucleotide repeat expansion, adds to the expanding knowledge on aetiology and pathogenesis. However, the challenge of elucidating the underlying causes and establishing effective disease-modifying therapies continues through active research. We review MND, focusing on clinical features, diagnosis and management.